Sexual quality of life and sexual self-efficacy among women during reproductive-menopausal transition stages and postmenopause: a comparative study - Hedyeh Riazi; Fatemeh Madankan; Seyed Ali Azin; Maliheh Nasiri; Ali Montazeri (BMC, 2021)
Abstract Sexual self-efficacy is essential for appropriate and desirable sexual function and sexual quality of life. This study aimed to compare sexual quality of life and sexual self-efficacy among women during reproductive-menopausal transition stages and postmenopause. This was a cross-sectional study of a sample of Iranian women. The sexual quality of life-female (SQOL-F) scale was used to measure sexual quality of life (SQOL) and sexual self-efficacy (SSE) was measured using the sexual self-efficacy questionnaire (SSEQ). Data were compared between the study groups using multiple linear regression. In all 340 women (170 in reproductive-menopausal transition stages and 170 postmenopause) were studied. The mean ages of reproductive-menopausal transition stages and postmenopausal women was 30.8 ± 6.55 and 56.3 ± 3.54 respectively (P < 0.001). Sexual self-efficacy and sexual quality of life were found to be significantly higher in reproductive-menopausal transition stages compared with postmenopause women (P < 0.001 and P = 0.017 respectively). Sexual and relationship satisfaction and sexual repression subscales differed significantly between the two groups (P = 0.001 and P < 0.001 respectively). Higher sexual self-efficacy contributed to higher sexual quality of life (P < 0.0001). Reproductive-menopausal transition stages women appear to enjoy higher levels of sexual self-efficacy and sexual quality of life. Given the importance of sexual quality of life, it is recommended to pay greater attention to sexual self-efficacy among postmenopausal women in order to improve sexual quality of life in this population.